2016
DOI: 10.15243/jdmlm.2016.034.609
|View full text |Cite
|
Sign up to set email alerts
|

Germination of seeds of some local pioneer plant species in different hydroseeding mulches for revegetation of post-coal mining soil

Abstract: The purpose of this study was to determine the hydroseeding mulch optimum compositions for germination and productivity of a few species of local plants pioneer in the post-mining land of coal from South Kalimantan. The method used in this research was by hydroseeding technique. The species observed were Crotalaria pallida, Cajanus cajan, Kyllinga monocephala, Paspalum conjugatum, Digitaria sanguinalis and Eleusine indica. Seven variations of mulch were added to the post-mining soil. Planting seeds carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…C. cajan seeds of Leguminosae just germinated in M 2 medium, in 3 DAS, with 20% of germination rate until 13 DAS. The similar result was reported by Azalia et al (2016) that C. cajan seeds were able to germinate in all mulch media with the fastest germination time in 3 DAS and the mean of seed germination starting time in all media occurred in 7 DAS. Baiti and Arisoesilaningsih (2015) reported that seeds of C. cajan sown in mulch media with 0.5 cm depth did not germinate at all.…”
Section: Germination Rate Among Local Species Seedssupporting
confidence: 90%
See 4 more Smart Citations
“…C. cajan seeds of Leguminosae just germinated in M 2 medium, in 3 DAS, with 20% of germination rate until 13 DAS. The similar result was reported by Azalia et al (2016) that C. cajan seeds were able to germinate in all mulch media with the fastest germination time in 3 DAS and the mean of seed germination starting time in all media occurred in 7 DAS. Baiti and Arisoesilaningsih (2015) reported that seeds of C. cajan sown in mulch media with 0.5 cm depth did not germinate at all.…”
Section: Germination Rate Among Local Species Seedssupporting
confidence: 90%
“…The seeds of Leguminosae showed a higher germination rate and a faster germination time compared to the seeds of Cyperaceae and Poaceae. This supported a finding of Azalia et al (2016) that the germination rate of Leguminosae seeds was higher and the germination time was faster than the rate and time of germination of Poaceae and Cyperaceae seeds.…”
Section: Germination Rate Among Local Species Seedssupporting
confidence: 89%
See 3 more Smart Citations